COMPREHENSIVE ASSESSMENT OF ANTIOXIDANT AND CHELATING CAPACITY OF SOME BIOGENIC AMINES AND RELATED DRUGS - GUIDEA, Alexandrina; MOȚ, Augustin Cătalin; SÂRBU, Costel (Studia Universitatis Babeș-Bolyai Chemia, 2020)
The radical scavenging, reducing power and metal-chelating capacity of some biogenic amines and related sympathomimetic drugs were clarified using various in vitro antioxidant assays as DPPH (1, 1-diphenyl-2-picryl-hydrazyl), ABTS (2,2’-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid), SORS (superoxide anion (O2-) radical-scavenging), nitric oxide (NO) radical scavenging, FRAP (ferric reducing antioxidant power), CUPRAC (cupric reducing antioxidant capacity) and CHROMAC (chromium reducing antioxidant capacity), including also FIC (ferrous ion-chelating capacity). The highest radical scavenging values in the case of DPPH test, for example, were obtained for methyldopa (93.14%), isoprenaline (92.92%) adrenalone (90.76%) and dopamine (90.51%). The highest reduction power, according to FRAP test, presented the same compounds: adrenalone (96.02%) methyldopa (95.97%), dopamine (94.67%) and isoprenaline (93.72%), except metaraminol (5.79%). Concerning the chelating capacity, adrenalone (66.35%), metaraminol (55.31%), metaproterenol (49.58%) and terbutaline (45.64%) showed the higher chelating capacity. The lowest value, in this case, was obtained for methyldopa (0.28%). According to the results obtained in the present study, the investigated drugs showed an effective in vitro antioxidant and radical scavenging ability and metal-chelating capacity. In addition, applying hierarchical cluster analysis (HCA), principal component analysis (PCA) and the sum of ranking differences (SRD) similarities and differences of investigated compounds and considered assays were clearly proved.